Social and Economic Conditions of Student Life in Europe Synopsis of indicators. Eurostudent V 2012-2015 - Hauschildt, Kristina (W. Bertelsmann Verlag, 2015)
"The EUROSTUDENT V - Synopsis of Indicators is the central publication of the EUROSTUDENT project and the result of the collaboration of a European-wide network including researchers, data collectors, representatives of national ministries, and other stakeholders. It comprises data from student surveys conducted in 29 countries in the European Higher Education Area during the fifth round of the EUROSTUDENT project. Adopting a broad, comparative perspective, the EUROSTUDENT V - Synopsis of Indicators provides information on topic areas such as access to higher education, study conditions, as well as international student mobility, assessment of studies, and future plans with the aim of inspiring policy debates and laying the ground for further research."